Brand Engagement Optimization: A Digital Marketing Approach in Changing Public Perception of the Directorate General of Customs and Excise - Yogi Darminto (Publikasi Indonesia, 2024)
This study aims to analyze the effectiveness of digital marketing strategies in increasing public perception of the Directorate General of Customs and Excise (DJBC) of Indonesia. As an important institution in national economic stability, DJBC has a dual role as a collector of state revenue, a trade facilitator, and an industry supporter. However, public trust in the DJBC has been affected by various negative factors. To improve its brand image, DJBC launched the